Differential thermosensitivity in mixed syndrome cardiac sodium channel mutants. (12th August 2015) - Abdelsayed, Mena; Peters, Colin H.; Ruben, Peter C.
Abstract : Key points: The E1784K mixed syndrome mutant of the cardiac voltage‐gated sodium channel, NaV 1.5, responds differently to temperature changes compared to the R1193Q mutant and wild‐type (WT) NaV 1.5. In E1784K, elevated temperature causes a larger increase in persistent current; there is also an increase in use‐dependent inactivation at 1 Hz, which is not apparent at 3 Hz. WT NaV 1.5 and R1193Q channels respond similarly to temperature changes. Action potential modelling (from extrapolated temperature coefficient ( Q 10 )values) predicts the effects of differential temperature sensitivity on the cardiac action potential: greater attenuation of the epicardial action potential occurs in E1784K as temperature shifts from hypothermic to hyperthermic conditions, and when transient outward potassium currents are increased. The results from the action potential model predict that, at febrile temperatures, E1784K channels results in a larger transmural voltage gradient. Hyperthermia exacerbates the Brugada syndrome 1 (BrS1) phenotype, which may be arrhythmogenic in E1784K mutants. Abstract: Cardiac arrhythmias are often associated with mutations in SCN5A the gene that encodes the cardiac paralogue of the voltage‐gated sodium channel, NaV 1.5. The NaV 1.5 mutants R1193Q and E1784K give rise to both long QT and Brugada syndromes. Various environmental factors, including temperature, may unmask arrhythmia. We sought to determine whether temperature might be an arrhythmogenic trigger in these two mixed syndrome mutants. Whole‐cell patch clamp was used to measure the biophysical properties of NaV 1.5 WT, E1784K and R1193Q mutants. Recordings were performed using Chinese hamster ovary (CHOk1) cells transiently transfected with the NaV 1.5 α subunit (WT, E1784K, or R1193Q), β1 subunit, and eGFP. The channels' voltage‐dependent and kinetic properties were measured at three different temperatures: 10ºC, 22ºC, and 34ºC. The E1784K mutant is more thermosensitive than either WT or R1193Q channels. When temperature is elevated from 22°C to 34°C, there is a greater increase in late I Na and use‐dependent inactivation in E1784K than in WT or R1193Q. However, when temperature is lowered to 10°C, the two mutants show a decrease in channel availability. Action potential modelling using Q 10 fit values, extrapolated to physiological and febrile temperatures, show a larger transmural voltage gradient in E1784K compared to R1193Q and WT with hyperthermia. The E1784K mutant is more thermosensitive than WT or R1193Q channels. This enhanced thermosensitivity may be a mechanism for arrhythmogenesis in patients with E1784K sodium channels. Abstract :